Analysis of Parenting Styles in Shaping Children’s Character - Hida Ayu Suranti; Hanif Cahyo Adi Kistoro (Linguanusa : Social Humanities, Education and Linguistic, 2026)
Introduction to The Problem: Parenting plays an important role in shaping children’s character; effective parenting requires appropriate methods and supporting factors. This study is motivated by the importance of parental parenting styles and school involvement in shaping students’ character. Purpose: This study aims to identify the parenting styles applied by parents, the methods used, and the factors influencing the character education of students. Design/methods/approach: This is a qualitative field research study using a descriptive approach. Data sources included students, parents, Ismuba (Islamic studies) teachers,and homeroom teachers at SD Muhammadiyah Jogodayoh. Data were  collected through observation, interviews, and documentation, and analyzed through three stages: data reduction, data display, and conclusion drawing. Findings: The results show that parents working as entrepreneurs applied both democratic and authoritarian parenting styles through various methods, including modeling, giving advice, attention/supervision, and habituation. The factors influencing students’ character formation include the role of parents/family, school/educators, the surrounding environment, and the development of social media.